2021
DOI: 10.1108/jcefts-06-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic virus on G8 countries’ financial indices based on artificial neural network

Abstract: Purpose The COVID-19 pandemic virus has affected the largest economies around the world, especially Group 8 and Group 20. The increasing numbers of confirmed and deceased cases of the COVID-19 pandemic worldwide are causing instability in stock indices every day. These changes resulted in the G8 suffering major losses due to the spread of the pandemic. This paper aims to study the impact of COVID-19 events using country lockdown announcement on the most important stock indices in G8 by using seven lockdown var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…However, making these right decisions is a complicated mission because many macroeconomic variables and international factors interact to influence the movement of stock markets indices and subindices into unanticipated levels. [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, making these right decisions is a complicated mission because many macroeconomic variables and international factors interact to influence the movement of stock markets indices and subindices into unanticipated levels. [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, many scholars have found that different generations of neural networks and artificial neural networks (ANNs) are the best prediction models for indices. ese models have high accuracy and help stakeholders make accurate decisions [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As such, Hongsakulvasu et al (2020) revealed that COVID-19 disquiet negatively influenced every kind of Thailand's stock return. Al-Najjar et al (2021) claimed that coronavirus incidents exert an adverse impact on equity market indices of G8 countries. Al-Qudah and Houcine (2021) noticed that the surge in established cases of COVID-19 negatively influenced stock returns for the main affected nations in the WHO Regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior papers were focused on volatility examination for African equity markets (Lo et al 2021;Takyi and Bentum-Ennin 2021;Zoungrana et al 2021), the Australian stock market (Brueckner and Vespignani 2021), BRICS and G7 states (Yu et al 2021), Canada and the US (Xu 2021), the Chinese stock market (Chen et al 2021;Liu et al 2021b;Shahzad et al 2021), seven emerging countries (Hashmi et al 2021), euro area stock markets (Duttilo et al 2021), the Indian financial market (Bora and Basistha 2021), the South Korea stock market (Hoshikawa and Yoshimi 2021), Thailand (Hongsakulvasu et al 2020), the Tunisian sectorial stock market (Fakhfekh et al 2021), the US stock market (Curto and Serrasqueiro 2021;Hong et al 2021), Vietnam and Philippines (Le and Tran 2021), Visegrad Group member states (Czech et al 2020), or several international markets (Al-Najjar et al 2021;Al-Qudah and Houcine 2021;Anser et al 2021;Banerjee 2021;Chowdhury et al 2021;Contessi and Pace 2021;Engelhardt et al 2021;Höhler and Lansink 2021;Rouatbi et al 2021;Szczygielski et al 2021b;Topcu and Gulal 2020;Vera-Valdés 2021;Youssef et al 2021;Zhang et al 2020). This paper aims to examine the volatility throughout the Romanian financial market during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Collins and Acta (2020) demonstrated that Dow Jones Industrial Average showed a reduction in mean stock prices during the COVID-19 period, on the other hands, Chinese Stock Exchange Composite Index showed an increase in mean stock prices. Hazem et al (2021) showed that the COVID-19 incidents had a negative impact on equity movement significantly, moreover, the U.S. lockdown and interest rate changes are the most affected by the G8 equity transactions, followed by Germany, France and the UK. Abu et al (2021) found that the number of confirmed cases of COVID-19 had a negative impact on stock market, however, the number of deaths had a positive one in the long-term.…”
Section: Existing Studiesmentioning
confidence: 99%